Performance Study of Ducted Air-Conditioning System with Different Mass Fraction of Al2O3Nanofluids - Husainy, Avesahemad; Gurav, Ankush R.; Pawar, Amit N.; Kate, Shridhar S.; Daphale, Dipak D.; Kirtane, Akash A. (Asian Review of Mechanical Engineering, 2019)
The coefficient of performance (COP) of VCR system is depends on the refrigeration effect and work required. It is increased by increasing the rate of heat transfer or by reducing the compressor work. Recently it is found that the use of nanotechnology in the refrigeration system can increase the performance of system. This research is on the concept, application, properties of the nanofluids & experimentation on ducted air conditioning system by using various mass fractions (0.25%, 0.50%, 0.75%, and 1.00 %.) of Al2O3 nanoparticles. In this experiment the nanoparticles are added into the base fluid which is lubricating oil (POE oil) of Compressor. It has been found that Nano lubricant has much higher temperature dependent thermal conductivity than conventional lubrication oil and it improves the thermo-physical properties. This can be considered as one of the key parameter of enhanced performance for refrigeration & air conditioning system. This research is performed in order to check and clarify the effect of Nano lubricant on the air conditioning system.